World war flu: war rhetoric of the Australian Prime Minister on coronavirus - Alyeksyeyeva, Iryna; Kaptiurova, Olena; Orlova, Vira (Penerbit Universiti Kebangsaan Malaysia, 2021)
During the coronavirus pandemic in spring 2020, political discourse was dominated by the language of war as the world’s political leaders saturated their speech with the terminology of war. This article examines some properties of the speech delivered by Australian Prime Minister Scott Morrison in the parliament on March 22, 2020. The general framework of the study is Critical Discourse Analysis (CDA) which investigates how language is used in ideological and social contexts and how it relates to power. The material of the research requires to apply a more specialised tool, namely Political Discourse Analysis (PDA) that examines the relation between language and political agendas and ideology. The study considers the political and ideological contexts of the speech through the entire political process and decision making at the national level as well as the sociopolitical and cognitive aspects of the speech in the parliamentary setting. In particular, attention is paid to the war rhetoric that induces the public to conceptualise the virus as an enemy and thus to present the crisis as a threat to the nation. The article explores language means employed by the speaker to actualise rhetorical strategies aimed at justifying his government’s measures taken to manage the crisis. To do this, the research looks into historical, cultural and psychological contexts of the speech as well as its political implicatures.